Positive Individual’s Socialization in the Intersection of Cultures and Religions: Narrative of Mimicry and Metamorphosis - Targamadzé, Vilija (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The aim of the article is to reveal the importance of individual’s positive socialization in the intersection of cultures and religions by disclosing the gap of mimicry and metamorphosis.
Keywords: cultures; metamorphosis; mimicry; positive socjalization; religions